The Effect of Giving Celery Decoction on Hypertension Reduction At Mutiara Health Center - Christiani, Meity; Umamy, Farida; Yunita, Sukma (International Journal of Public Health Excellence (IJPHE), 2022)
Hypertension has been designated a "silent killer" due to its asymptomatic nature. Hypertension is typically asymptomatic, meaning that it occurs without any noticeable symptoms. One of the herbs that has been demonstrated to possess antihypertensive properties is celery. As a hypotensive agent, celery has been demonstrated to reduce blood pressure in patients with hypertension. The objective of this research is to investigate the potential efficacy of celery in lowering blood pressure. The objective of this study is to ascertain the impact of celery boiled water on blood pressure in patients with hypertension. The research methods employed in this study are as follows: This research is quantitative and employs a quasi-experimental design with a one-group pretest-posttest. The population under investigation in this study consisted of individuals with hypertension who were attending the Mutiara Health Center. The sample size was 50 individuals, selected using a non-random sampling technique with a purposive sampling approach. The instruments utilized in this study are a spygmonanometer and stethoscope. The results of the blood pressure examination are documented in the observation sheet. The results of the statistical tests, in the form of a paired t-test, conducted before and after the administration of celery boiled water, yielded a p-value of 0.001, which was less than the alpha value of 0.05. This indicates that there is a statistically significant difference between the two groups. Based on these findings, it can be concluded that the hypothesis (H1) is accepted, suggesting that there is an effect of celery boiled water on blood pressure in pre-elderly individuals with hypertension at Mutiara Health Center.